Psychological impacts of COVID-19 pandemic in cancer patients on active treatment. Issue 8 (August 2022) - Koca, Sinan; Koca, Esra; Okten, Ilker N.; Orengül, Fatma FC.; Oztürk, Akın; Ozçelik, Melike; Oyman, Abdilkerim; Çil, Ibrahim; Gümüş, Mahmut
Abstract: Introduction: Although cancer patients have a high risk of exposing COVID-19 and developing severe complications, they have to receive active treatment. We aimed to determine the psychological conditions of cancer patients and shed light on the establishment of early psychological intervention and intervention policies by making specific recommendations. Method: We consecutively evaluated 385 cancer patients under treatment. Post-traumatic stress disorder (PTSD) symptoms, depression, anxiety, stress, and associated sociodemographic/clinical characteristics were investigated. In addition, we applied depression-anxiety-stress-scale-21 (DASS-21) for the mental states of patients and Impact of Event-Scale-Revised (IES-R) for the psychological effects of Covid-19. Results: The mean age was 58 (18–88). 47.2% were psychologically distressful per DASS-21, and 39.3% were traumatic per IES-R scores. 71.9% stated the risk of getting COVID-19 was high since they had cancer, and 82% stated serious complications would develop if they had COVID-19 infection. Patients diagnosed for more than one year were more stressed, anxious, and depressive (p–value = 0.001, 0.003, 0.049, respectively). Singles were more stressed, depressed, and traumatized than couples (p-value = 0.001, 0.011, 0.001). In multivariate analysis, a significant correlation with being under psychiatric treatment before the pandemic was found for depression (OR: 3.743, 95 %CI: 1.790–7.827) anxiety (OR: 3.776–95 %CI: 1.945–7.332) and stress levels (OR: 4.129, 95 %CI: 1.728–9.866). Having relatives who died or received treatment for COVID-19(OR: 0.515, 0.296–0.895) and being unmarried (OR: 2.445–95% CI: 1.260–4.747) predicts PTSD development. Conclusions: When the psychological effects of the COVID-19 pandemic are manifesting strongly, cancer patients' anxiety and exposure levels are high. It is of great importance that clinicians understand needs, recognize psychological distress, and direct them to relevant departments for supportive care. Highlights: Examined 385 cancer patients under active treatment during the COVID-19 era. Investigated Post-traumatic stress disorder (PTSD) symptoms, depression, anxiety, stress, and associated sociodemographic/clinical characteristics. Performed depression-anxiety-stress-scale-21 (DASS-21) for mental states, Impact of Event-Scale-Revised (IES-R) for psychological effects of Covid-19. Being single, having relatives died of COVID-19 and being under psychiatric medication before the pandemic give tendency to depression and anxiety. Abstract : Covid-19, Cancer, Chemotherapy, Psychological impact.